PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING DALAM MATERI TARI TRADISIONAL UNTUK MENINGKATKAN APRESIASI SISWA KELAS VII SMP NEGERI 1 LUBUK BARUMUN - Torina Pulungan; Dilinar Adlin; Irwansyah Irwansyah (Gesture: Jurnal Seni Tari, 2020)
ABSTRACT This study aims to describe the snowball throwing learning model in traditional dence material to increase the appreciation of students of calass VII SMP Negeri 1 Lubuk Barumun. The theory used in this study is the snowballthrowing theory by Miftahul Huda and the understanding of apreciation by Sunarto and Suherman. The research method used in this study is a quantitative descriptive method by using the pretest-posttest design group that is eksperiments with one group or one class VII SMP Negeri 1 Lubuk Barumun amounting to 192 students, while the sampel in this study is class VII-1. Techniques for collecting data on observation , documentation, library research. The research instrument used was a list of question totaling 10 questions that had been tested for validation that would be used at the time of the pretest and posttest. Before the action is taken, the pretest test is conducted to determine the students initial abilities. The result of pretest data analysis showed that the average value abtained was 41,3 with a standard deviation of 22,258. After the snobwall throwing learning model was applied posttest. The results abtained are average student scores have increased to 87 with a standart deviation of 468,509. From the average result it can be seen that the increase in the percentage of the pretest to the posttest for students apreciation is an in crease 45,7%. T test is used to see the level of student appreciation from the results of the Ttest at the level ofabtained > that is (11,297 > 1,67115) then  is rejected and  is accepted. That is the result of student appreciation in the posttest after using the snowball throwing learning model. It can be councluded that the aplication of the model aplication of the snowball throwing learning model tor-tor naposo nauli bulung learning can increase the preciation of class students VII-1 SMP Negeri 1 Lubuk Barumun. Keywords: Snowball Throwing, Tor-tor Naposo Nauli Bulung, Appreciation.